Wood destroying agent: marine borer / Maryani Mohamad @ Shafie - Mohamad @ Shafie, Maryani (2008)
Marine borers are organisms that live in seawater or brackish water and are capable of destroying wood. There are two general types of marine borers; Crustacean and Mollusca. Molluscan borers are related to oysters and clams have three important of wood-boring mollusks. The teredines, Teredo and Bankia, are commonly referred to as "shipworm" because of their wormlike appearance. Borers of the genus Martesia resemble clams in general appearance and are distinct from Teredo and Bankia in number of respect. The crustaceans (Crustacea) include various familiar animals, such as lobsters, crabs, shrimp, crayfish and barnacles. Limnoria or gribble is in family of Limnoridae have mouth parts that include a pair of strong, toothed mandibles designed for chewing wood, which is utilized for wood along with the marine fungi and possibly bacteria the wood contains. And Sphaeroma or Pill Bugs have the same general structure as gribble but are much larger and stouter.